The role of changing health in rising health-related benefit claims - Eduin Latimer; Sam Ray-Chaudhuri; Tom Waters (Institute for Fiscal Studies (IFS), 2025)
Since the COVID-19 pandemic, there has been a significant rise in the number of people getting health-related benefits. In England and Wales, 4 million 16- to 64-year-olds (1 in 10) now claim either disability or incapacity benefits, up from 2.8 million in 2019 (1 in 13). One potential contributor to these trends is worsening health. In this report, we consider what we can learn from various sources about what has happened to working-age health since the pandemic, taking into account the difficulties surveys have had over the past few years.
Keywords: 330; Health and social care; Taxes and benefits; Benefits; Disability; Health; Working age benefits; Measurement